SOSIALISASI PENANAMAN TANAMAN OBAT KELUARGA DAN MINUMAN HERBAL UNTUK MENINGKATKAN DAYA TAHAN TUBUH WARGA KELURAHAN KRAMATINGGIL GRESIK MELALUI PLATFORM YOUTUBE - Erlyana Desy Rahmawati; Devita Inka Amalia; Lutvi Niswa Octaviana; Rika Nur Azizah; Tresna Maulana Fahrudin (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2022)
During the current COVID-19 pandemic, people are required to have a good immune system. To gain immunity, people can consume herbal drinks that can be made from the harvested plants of TOGA. Various types of TOGA plants that can be used such as lemongrass, turmeric, ginger, and java ginger. This plant can be planted in a narrow area or in a pot that can be placed in the yard of the house. This is in line with the condition of Kramatinggil Urban Village in Gresik District which does not have a large area as a planting medium so they can take advantage of the yard. The purpose of planting TOGA is to familiarize residents with planting original spices from Indonesian crops and processing herbal drinks in order to increase the immune system, especially for protection from COVID-19. The results of the program showed that TOGA planting video was watched 60 times and the video for making herbal drinks was watched 47 times by local residents. In addition, 30 bottles of herbal drinks have been distributed to residents of Kramatinggil Urban Village.